PREVALENCE OF MUTATIONS IN ELANE, GFI1, HAX1, SBDS, WAS, AND G6PC3 IN PATIENTS WITH SEVERE CONGENITAL NEUTROPENIA - Xia, Jun (2009)
Severe congenital neutropenia (SCN) is a genetically heterogeneous syndrome associated with mutations of ELANE (ELA2), HAX1, GFI1, WAS, CSF3R or G6PC3. We investigated the prevalence of mutations of ELANE in a cohort of 162 SCN patients for whom blood or bone marrow samples were submitted to the North American Severe Chronic Neutropenia Tissue Repository. Mutations of ELANE were found in 90 of 162 patients (55.6%). Subsequently, we conducted an analysis of a subset of 73 of these cases utilizing a high throughput sequencing approach to determine the prevalence of other mutations associated with SCN. Among the 73 patients, mutations of ELANE were detected in 28. In the remaining 45 patients with wild type ELANE alleles, 5 patients had mutations: GFI1 (1), SBDS (1), WAS (1) and G6PC3 (2); no mutations of HAX1 were detected. In approximately 40% of our cases, the genetic basis of SCN remains unknown. These data suggest that for genetic diagnosis of SCN, ELANE genotyping should first be performed. In patients without ELANE mutations, other known SCN-associated gene mutations will be found rarely and genotyping can be guided by the clinical features of each patient.